Exploring the photometric variability of ultra-cool dwarfs with TESS - Petrucci, Romina Paola (2024)
We present a photometric characterization of 208 ultra-cool dwarfs (UCDs) with spectral types between M4 and L4, from 20-s and 2-min cadence TESS light curves. We determine rotation periods for 87 objects (⁠~42%⁠) and identify 778 flare events in 103 UCDs (⁠~49.5%). For 777 flaring events (corresponding to 102 objects), we derive bolometric energies between 2.1 × 10^30 and 1.1 × 10^34 erg⁠, with 56 superflare events. No transiting planets or eclipsing binaries were identified. We find that the fraction of UCDs with rotation and flaring activity is, at least, 20 per cent higher in M4–M6 spectral types than in later UCDs (M7–L4). For spectral types between M4 and L0, we measure the slope of the flare bolometric energy–duration correlation to be γ = 0.497 ± 0.058, which agrees with that found in previous studies for solar-type and M dwarfs. Moreover, we determine the slope of the flare frequency distribution to be α = −1.75 ± 0.04 for M4–M5 dwarfs, α = −1.69 ± 0.04 and α = −1.72 ± 0.1 for M6–M7 and M8–L0 dwarfs, respectively, which are consistent with previous works that exclusively analysed UCDs. These results support the idea that independently of the physical mechanisms that produce magnetic activity, the characteristics of the rotational modulation and flares are similar for both fully convective UCDs and partially convective solar-type and early-M stars. Based on the measured UCD flare distributions, we find that ultraviolet radiation emitted from flares does not have the potential to start prebiotic chemistry.